2016
DOI: 10.1111/cbdd.12770
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Imidazolium‐Based Ionic Liquids Investigated by QSAR Modeling and Experimental Studies

Abstract: Predictive QSAR models for the inhibitors of B. subtilis and Ps. aeruginosa among imidazolium-based ionic liquids were developed using literary data. The regression QSAR models were created through Artificial Neural Network and k-nearest neighbor procedures. The classification QSAR models were constructed using WEKA-RF (random forest) method. The predictive ability of the models was tested by fivefold cross-validation; giving q(2) = 0.77-0.92 for regression models and accuracy 83-88% for classification models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Classification and regression QSAR models with good predictive power with accuracy over 88 % and a coefficient Q 2 0.77-0.92 were designed (Hodyna et al, 2016a). The obtained model of antibacterial activity of imidazolium-based ILs was stored in the OCHEM database (www.ochem.eu) and assisted in searching for new potential antimicrobial agents against B. subtilis and Ps.…”
Section: Other Theoretical Molecular Descriptorsmentioning
confidence: 99%
“…Classification and regression QSAR models with good predictive power with accuracy over 88 % and a coefficient Q 2 0.77-0.92 were designed (Hodyna et al, 2016a). The obtained model of antibacterial activity of imidazolium-based ILs was stored in the OCHEM database (www.ochem.eu) and assisted in searching for new potential antimicrobial agents against B. subtilis and Ps.…”
Section: Other Theoretical Molecular Descriptorsmentioning
confidence: 99%
“…Similarly, ANN and RF were applied for the creation of a prediction model of Pseudomonas aeruginosa and Bacillus subtilis inhibitors using bibliographical data of imidazolium‐based ionic liquids . Twenty theoretically active synthesis compounds of 1,3‐dialkylimidazolium ionic liquids were assayed.…”
Section: Qsar In Antibacterial Compound Developmentmentioning
confidence: 99%
“…Similarly, ANN and RF were applied for the creation of a prediction model of Pseudomonas aeruginosa and Bacillus subtilis inhibitors using bibliographical data of imidazolium-based ionic liquids. 50 Twenty theoretically active synthesis compounds of 1,3-dialkylimidazolium ionic liquids were assayed. It was observed that, for asymmetric compounds, only those with at least one radical containing a 12-carbon alkyl chain showed high antibacterial activity.…”
Section: Qsar In Antibacterial Compound Developmentmentioning
confidence: 99%
“…Later, several researchers developed QSAR models for predicting bacterial toxicity values based on linear regression methods using different types of molecular descriptors [5, 13, 20]. Hodyna et al [31] developed classification and regression QSAR models with good accuracies, among them the classification method led to better results than the latter [31]. In 2018, He et al [30] presented a QSAR model to predict MIC and MBC values of ILs toward S. aureus.…”
Section: Qsar For the Response Of Bacteriamentioning
confidence: 99%